PHYSICS LEARNING MODELS BASED ON SYNECTIC TO IMPROVE PROBLEM-SOLVING SKILLS: A NEED ANALYSIS - Rufaida, Salwa; Syam, Husain; Samad, Sulaiman (Physical and Mathematical Education, 2023)
This study aims to describe the development needs of physics learning models based on Synectic in improving problem-solving abilities. Formulation of the problem. The design of physics learning models based on Synectic directs students in getting used to processing creative thinking to achieve higher-order thinking skills, one of which is problem-solving ability. The Synectic learning model implementations are identical to analogy and metaphoric thinking. Analogies and metaphor thinking will help students understand abstract concepts to become more contextual, making it easier for students to solve the problem. Materials and methods. This research type is research and development with the ADDIE design. The learning model needs an analysis description performed during the analysis stage by determining the gap between the real conditions and the desired ideal conditions in learning physics, especially in college. The needs analysis research was carried out at the Muhammadiyah University of Makassar with two lecturers and twelve students as research respondents for three months in the even semester of the 2021/2022 academic year. The needs analysis data collection using interview guidelines, literature reviews, and questionnaires. The data collection results will be analyzed with a qualitative descriptive analysis. Results. The reality and ideal conditions description obtained from the results of curriculum analysis, student characteristics, and lecturer abilities in implementing physics learning in college. The needs analysis results show a gap between reality and the desired ideal conditions in learning physics. Conclusions. Even though the ability to solve problems is one of the expected learning outcomes based on curriculum achievement indicators and skills needed at this time based on a person’s cognitive stage at the age of college students. Therefore, a physics learning model based on Synectic development is very needed and indicated by the student’s tendency ability to solve physics problems to be low. It means synergizing between teachers and students for creative thinking is needed in learning physics as an important basis for improving problem-solving skills.